High pressure phase equilibria of supercritical alcohols with triglycerides, fatty esters and cosolvents - Hegel, Pablo Ezequiel (2008)
The transesterification of vegetable oils, esterification of fatty acids and glycerolisis reactions, with supercritical alcohols, are of interest in the production of fine chemicals and biodiesel. The partial miscibility between the reactants and products of these processes have raised interest in the multiple phase behavior under reaction and separation conditions of mixtures of triglycerides and derivatives, fatty esters, alcohols and glycerin. In the present work, recent experimental studies under separation and reaction conditions are compared with modeling predictions using a group contribution with association equation of state.